Sex differences in anxiety-like behavior and locomotor activity following prenatal and postnatal methamphetamine exposure in adult rats - Hrubá, L; Schutová, B; Šlamberová, R (Physiology & behavior, 2012)
The aim of the present study was to investigate the impact of prenatal and postnatal methamphetamine (MA) exposure on behavior and anxiety in adult male and female rats. Mothers were daily exposed to injection of MA (5 mg/kg) or saline (S): prior to impregnation and throughout gestation and lactation periods. On postnatal day 1, pups were cross-fostered so that each mother raised 6 saline-exposed pups and 6 MA-exposed pups. Based on the prenatal and postnatal exposure 4 experimental groups (S/S, S/MA, MA/S, MA/MA) were tested in the Open field (OF) and in the Elevated plus maze (EPM) in adulthood. Locomotion, exploration, immobility and comforting behavior were evaluated in the OF, while anxiety was assessed in the EPM. While prenatal MA exposure did not affect behavior and anxiety in adulthood, postnatal MA exposure (i.e. MA administration to lactating mothers) induced long-term changes. Specifically, adult female rats in diestrus and adult males postnatally exposed to MA via breast milk (S/MA and MA/MA) had decreased locomotion and exploratory behavior in the OF and showed increased anxiety-like behavior in the EPM when compared to female rats in diestrus or males postnatally exposed to saline (S/S and MA/S). In adult females in proestrus, postnatal exposure to MA affected only exploratory behavior in the OF when compared to rats in proestrus postnatally exposed to saline. Thus, the present study shows that postnatal exposure to MA via breast milk impairs behavior in unfamiliar environment and anxiety-like behavior of adult male and female rats more than prenatal MA exposure.
Keywords: těhotenství; Exploratory Behavior; tonická imobilita; bludiště - učení; zpožděný efekt prenatální expozice; Anxiety; mateřské chování; Sex Characteristics; Animals, Newborn; Dopamine Uptake Inhibitors; Female; estrální cyklus; krysa rodu Rattus; Video Recording; analýza rozptylu; Maternal Behavior; pohybová aktivita; Analysis of Variance; Maze Learning; pátrací chování; úzkost; methamfetamin; Immobility Response, Tonic; Disease Models, Animal; audiovizuální záznam; Motor Activity; novorozená zvířata; pohlavní dimorfismus; mužské pohlaví; Prenatal Exposure Delayed Effects; zvířata; Pregnancy; inhibitory vychytávání dopaminu; ženské pohlaví; Rats; Animals; Methamphetamine; Male; Estrous Cycle; modely nemocí na zvířatech